(untitled) (American Journal of Pedagogical and Educational Research, 2026)
This study examined the impact of Business Education students’ application of instructional resources on academic performance in tertiary institutions. It was guided by two research questions and two null hypotheses. The researcher adopted the descriptive survey as the design for the study. The population of the study comprised Business Education respondents from the 2024/2025 academic session in public tertiary institutions offering Business Education programme. Two hundred and twenty-seven (227) undergraduate Business Education students were the sample size for the study. Findings of the study revealed amongst others that there is a significant positive correlation between the availability of instructional resources and Business Education student’s performance in tertiary institutions. The study concluded and recommended that instructional resources as a vital ingredient, should be made available to student and employed in the pedagogical process as it is capable of enhancing students’ performance.